Antimicrobial resistance of heterotrophic marine bacteria isolated from seawater and sands of recreational beaches with different organic pollution levels in southeastern Brazil: evidences of resistance dissemination - Fernandes Cardoso de Oliveira, Ana Julia [UNESP]; Ranzani de Franca, Paula Thais [UNESP]; Pinto, Aline Bartelochi [UNESP] (Springer, 2010)
Antimicrobial resistance of marine heterotrophic bacteria to different antimicrobials agents were evaluated in seawater, dry and wet sands from three marine recreational beaches with different pollution levels. In all studied beaches, the greatest frequencies of resistance were found in relation to penicillin. on Gonzaguinha, the most polluted beach, 72.3% of all isolated strains showed simple resistance, whilst 8.33% had multiple resistance. The values found on Ilha Porchat beach, were 70.8% and 6.9% for simple and multiple resistances, respectively. on GuaraA(0), the less polluted beach, only 35.3% of isolated strains had simple resistance. Multiple resistance was not observed. While samples from Gonzaguinha and Ilha Porchat beach showed isolated strains resistant to seven and six different antimicrobial agents, respectively, samples from GuaraA(0) beach were resistant only to penicillin and erytromicin. The positive correlations obtained between the degree of seawater contamination and frequency and variability of bacterial resistance indicate that polluted marine recreational waters and sands are sources of resistant bacteria contributing thus, to the dissemination of bacterial resistance.
Keywords: Marine heterotrophic bacteria; Resistance; Seawater; Sand beach; Contamination